TASTE LEVEL OF FISH DRUMSTICK “DRAGON FEET” MADE FROM LARGE PELAGIC FISH MEAT - Junianto, Junianto; Gunawan, Nesya Putri; Damayanti, Yohana; Wijayanto, Rahmat (Jurusan Perikanan dan Kelautan, 2024)
The vast potential of Indonesia's seas makes fish a vital food source, contributing significantly to food availability in the country. Among the commonly caught species are large pelagic fish, such as tuna, skipjack tuna, and mackerel. To diversify processed fish products, large pelagic fish are transformed into innovative products, including